General Income Tax Article 23 - Galuh Tresna Murti; Selvia Eka Restu; Vina Aprilia Nursari; Widialestari Widialestari (Jurnal Riset Perpajakan: Amnesty, 2023)
This Journal discusses about Income Tax (PPh) 23. This journal use qualitative methods with the type of document study research. PPh Article 23 or PPh 23 is a type of income tax (pph) in indonesia. In short, PPh 23 is a tax that is imposed on income on capital, participation in services, prizes, interest, dividends, riyals, or prizes and awards, other than those deducted from PPh Article 21. This type of income occurs due to transactions between parties who provide income and the party receiving the income